PENGARUH STRUKTUR KEPEMILIKAN SAHAM, FREE CASHFLOW DAN RISIKO TERHADAP DIVIDEND POLICY DAN AGENCY COST SERTA DAMPAKNYA TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN YANG LISTED DI BURSA EFEK INDONESIA) - Isti Fadah (UMSurabaya Publishing, 2007)
The goals of the research are to test : 1) the enfluence of ownership structure to dividend policy. 2) the enfluence of ownership structure to agency cost. 3) the enfluence of risk to dividend policy.4) the enfluence of risk to agency cost. 5) the enfluence of free cash flow to dividend policy. 6) the enfluence of free cash flow to agency cost. 7) the enfluence of dividend policy to firm value. 8) the enfluence of agency cost to firm value.The test result with SEM ( structural equation model) analysis show that for test of goodness of fit overall model give a value Chi Square 39.757 and p value 0.135 (cut off < 0,05) it means that the model is good. The other criterion give a value RMSEA = 0,046 (cut off £ 0,08), GFI = 0,945 (cut off ³ 0,08) and AGFI = 0,903 (cut off ³ 0,08). It means that hypothetic model conseptually and teoritically is supported of empirical data and the model is feasable to be used. The result of structural model for testing of hypothesis show that only H5 (Free cash flow significantly enfluence dividend policy) and H6 (Free cash flow significantly enfluence agency cost) are statisticly proven each with p value fix and 0.000Keywords : ownership structure, dividend, agency cost